1983
DOI: 10.1620/tjem.140.181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gefarnate on endogenous prostacyclin, prostaglandin E2 and thromboxane in water-immersed rats.

Abstract: The level of endogenous prostacyclin (PGI2), prostaglandin E2 (PGE2) and thromboxane A2 (TXA2) in rat gastric mucosa was determined by radioimmunoassay to examine whether gefarnate, an antiulcer agent, maintained the endogenous prostaglandin (PG) level in rats subjected to waterimmersion stress. Seven-hr immersion induced gastric lesions and a marked reduction in PGI2 and PGE2. When gefarnate was injected subcutaneously before stress exposure, the mean ulcer index was reduced and the PGI2 and PGE2 levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Tsukada et al 20) observed in in vitro experiments that higher concentration of ethanol (0.5-1.5 M) caused a marked reduction in mucus glycoprotein synthesis and that the addition of ornoprostil, a PGE 1 analog, improved the synthesis and secretion of glycoprotein in the presence of ethanol. In connection with mucus glycoprotein synthesis, Kobayashi et al 21) reported that water-immersion stress lasting 7 h in rats induced gastric lesions and a marked reduction in endogenous PGE 2 and prostaglandin I 2 (PGI 2 ) levels. In addition, they demonstrated that gefarnate, an anti-ulcer agent, inhibited water immersion-induced gastric lesions and the reduction of PGE 2 and PGI 2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Tsukada et al 20) observed in in vitro experiments that higher concentration of ethanol (0.5-1.5 M) caused a marked reduction in mucus glycoprotein synthesis and that the addition of ornoprostil, a PGE 1 analog, improved the synthesis and secretion of glycoprotein in the presence of ethanol. In connection with mucus glycoprotein synthesis, Kobayashi et al 21) reported that water-immersion stress lasting 7 h in rats induced gastric lesions and a marked reduction in endogenous PGE 2 and prostaglandin I 2 (PGI 2 ) levels. In addition, they demonstrated that gefarnate, an anti-ulcer agent, inhibited water immersion-induced gastric lesions and the reduction of PGE 2 and PGI 2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…10) However, it has been shown that when gefarnate (100 mg/kg/d) is subcutaneously administered to normal rats for 7 d, no significant increases in prostaglandin E 2 and prostacyclin levels occur in the gastric mucosa. 54) We have reported that pretreatment with a low dose of indomethacin (5 mg/kg), which is known to inhibit prostaglandin production, but not to induce gastric mucosal lesions, had no effect on the formation and progression of C48/80-induced gastric mucosal lesions in rats.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports showing that gefarnate exerts a protective effect against acute gastric mucosal lesions in various in vivo experimental models such as gastric mucosal lesions induced by histamine-antihistamine, immobilization, reserpine, fasting, ethanol, asprin, HCl-asprin, HCl-ethanol, HCl-taurocholate, and WIRS. [3][4][5][6][7][8][9][10] Hara et al 6) showed that when pylorus-ligated rats with oral HCl-asprin treatment received a single oral pre-administration of gefarnate, this drug exerted a protective effect against gastric mucosal lesions with attenuation of decreased gastric mucosal hexosamine content. In addition, Kobayashi et al 10) reported that gefarnate prevented WIRS-induced ulcer formation by inhibiting the reduction of endogenous prostaglandin E 2 and prostacyclin (prostaglandin I 2 ) levels.…”
mentioning
confidence: 99%
“…The homogenizes was washed out with 10 ml chloroform, the resultant solution was mixed vigorously with homogenate and allowed to stand for 30 min at room temperature. PGs and TX were extracted as has been described (Kobayashi et al 1983). The solution was filtrated and washed with Folch's solution (CHC13-CH3OH; 2:1 by volume) and evaporated to dryness at 40°C under a nitrogen stream.…”
Section: Methodsmentioning
confidence: 99%
“…This protection has been called "cytoprotection" (Robert 1976;Whittle 1976;Carmichael et al 1977;Robert et al 1979). Gefarnate, an isoprenoid whose anti-ulcer action is due to its protection of the gastric mucosa, has recently been shown to inhibit the decrease of the gastric mucosal PGI2 and levels in rats stressed by water-immersion (Kobayashi et al 1983). …”
mentioning
confidence: 99%